Kōan-like ambiguities in John Cage's Electronic Music for Piano: a novel application of formal concept analysis. Issue 1 (2nd January 2017) - Fowler, Michael D.
Abstract : In this article I present a novel application of Formal Concept Analysis (FCA) to the problem of interpreting and analysing the non-standard graphical music score Electronic Music for Piano (1965) by American composer John Cage. The avant-garde nature of Cage's score, presented on a single page as a series of anecdotal texts written in natural language, resists traditional approaches of music theory analysis. I utilise FCA for its suitability for delving into the work's taxonomy as well as its ability to visualise and analyse semiotic patterns and relationships within the natural language text fragments of the work. In this regard, FCA is also used as a means in which to frame what many writers have previously identified as kōan -like qualities in many of Cage's works. A kōan is generally understood as a type of unsolvable Zen Buddhist riddle filled with contradictions and ambiguities. I subsequently theorise Electronic Music for Piano as a type of musical kōan, and by applying FCA, demonstrate how various derived formal concepts, object extensions, and subset groupings of the work support this theory.